Investigation of Water Quality and Lighting in Hydroponic Systems - Tze Ching Ong; Yoong Chow Ho; Andy anak Buja (Hasanuddin University, 2026)
Hydroponic systems offer numerous benefits, including faster plant growth, higher yields, and efficient water and nutrient use. They are also ideal for urban farming and areas with poor soil quality, as they reduce the need for pesticides and minimize land use. The significance of water quality and lighting in hydroponic systems cannot be overstated, as these factors are crucial for maximizing productivity and ensuring sustainable crop production. Therefore, this study investigated the impact of water quality and lighting on hydroponic systems to optimize plant growth and yield. The initial work examined how variations in the type of water, namely tap water, rainwater, and river water, affect green bean growth. Subsequently, the best kind of water was used in the self-designed and fabricated hydroponic system to investigate the effects of white and purple light by measuring the growth of lettuce plants. Findings revealed a strong correlation between water quality and plant growth, with river water under purple light demonstrating a higher growth mean score of 0.90 cm for lettuce compared to rainwater, possibly due to nutrients and trace minerals sourced from the surrounding environment. This study underscores the importance of water quality and lighting selection in hydroponic systems to ensure maximum productivity. By optimizing these simple parameters, farmers can achieve higher yields and more efficient resource use, contributing to the sustainability of agricultural practices.